Measuring and exploring factors affecting students' willingness to engage in peer mentoring. Issue 2 (6th June 2014) - Noufou, Ouedraogo; Rezania, Davar; Hossain, Muhammad
Abstract : Purpose: – The purpose of this paper is to measure students' willingness to mentor their peers and explores key factors to student peer mentoring effectiveness. Design/methodology/approach: – The paper uses a hybrid research methodology consisting of a survey and a focus group discussion. The survey was conducted with students of a bachelor of commerce (BCom) program of a North American university to analyze the impact of organizational culture and altruism on their willingness to mentor their peers. The focus group discussion was carried out with students of the same program to explore the objectives, focus, and factors contributing to their willingness to mentor and to peer mentoring effectiveness. Findings: – Organizational culture and altruism significantly affect students' emotional and intentional willingness to mentor their peers. Peer mentoring can help students prepare their transition from high school to university, guide them through university programs, and help them prepare their transition from university to workplace. Critical factors to peer mentoring effectiveness include a good fit between mentors and mentees, a reasonable ratio of mentor to protégés, and an understanding of and a willingness to address each student's specific needs. Practical implications: – Business schools should embrace and promote a culture of mutual help, look for altruistic students as prospective peer mentors, and promote voluntary student peer mentoring. A mentoring program should be flexible enough to meet each student's needs. Attention should be paid to finding a good fit between mentors and protégés. Communication should focus on the benefits of student peer mentoring for mentors and protégés. Originality/value: – This research brings empirical evidence on peer mentoring by testing and confirming the impact of altruism and organizational culture on students' willingness to mentor their peers. It also provides practical insight to business schools for implementing student peer mentoring programs.